THE RELATIONSHIP BETWEEN INDUSTRIAL ESTATE AND RURAL DEVELOPMENT (AN EVALUATION OF PJT’S CSR) - Genoveva, Genoveva; Purwanti, Anastasia; Pratama, Kevin; Akbar, Aris (Jurnal Bakti Masyarakat Indonesia, 2018)
The existence of industrial estates should have a positive impact on the surrounding community. But not all people can feel the positive impact of the existence of industrial estates. The industrial area in this study is Jababeka Cikarang industrial area where there are more than 1600 companies. One large company, PJS, which has been carrying out corporate social activities (CSR) for more than 5 years in collaboration with President University, conducted research to find out the effectiveness of the CSR they have done, especially in 3 villages located in ring 1 (the location closest to the area industry). The study was conducted with qualitative methods, namely in-depth interviews with villagers who were representatives of each village as many as 35 people. The questions were tested for validity and reliability with triangulation, namely the PJS company partners and the Village Heads from the 3 villages that became the research object. From the tri buttom line approach the results of the research show that both socially (people), environment (planet) and economic (profit) have not had a significant impact on the villagers.